MECHANISATION AND AUTOMATION IN CONTACT WELDING (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The main task of control devices in contact welding is to implement the given program in a certain time by transmitting control signals in analog or discrete form to the functional nodes of the control devices.